Correlation between interleukin-6 and septic shock in children - Stephanie Yulianto; Ari Runtunuwu; Vivekenanda Pateda; Jose Mandei; Julius Lolombulan (Indonesian Pediatric Society, 2012)
Background Sepsis is a lifeô€†threatening condition and the mostcommon cause of death in intensive care units in developingcountries, such as Indonesia. The first clinical signs of sepsis areusually nonô€†spedfic. More specific signs and laboratory parametersoften occur late and are associated 'With organ dysfunction andhigh mortality rates. Interleukinô€†6 (IL–6) is a biomarker reported tobe superior to clinical signs and conventional tests for sepsis. IL–6levels may indicate microorganism invasion, as well as progressionof infection into sepsis, severe sepsis, and septic shock.Objective To evaluate a correlation between interleukin (IL)ô€†6and septic shock in childrenMethods This crossô€†sectional study was conducted in the pediatricintensive care unit of Prof. Dr. R.D. Kandou Hospital, Manado,between June to September 2011. Subjects were children withsepsis or septic shock aged 1 month to 13 years, v.ith diagnosesbased on the International Pediatric Sepsis Consensus ConferenceCriteria 2005. A oneô€†time measurement of IL–6 plasma levelswas done at the time of diagnosis. Data was analyzed by logisticregression test using SPSS version 17 software. A P value of <0.05indicated statistical significance.Results The mean IL–6 plasma level in the septic group was 1.68(95%CI 1.45 to 1.91) pg/mL and that of the septic shock groupwas 2.33 (95%CI 1.79 to 2.86) pg/mL. Our results showed astrong positive correlation between ILô€†6 plasma levels v.ith theprobability of septic shock in children v.ith sepsis (regressioncoefficientô€‡1.3lO, Pô€‡O.024).Conclusion Higher plasma IL–6 levels were associated v.ith ahigher risk of septic shock in children with sepsis. [Paediatrrndones.2012;52:352-5].